Rector and the First Teacher of German school of Yekaterinburg Bernhard Stermer (1735-1740) - A. M. Safronova (Научный диалог, 2019)
The problem of hiring a foreign teacher in one of the first foreign language schools of provincial Russia, the German school of Yekaterinburg, and his activities is considered. The particular interest in hiring B. Stermer is explained by the fact that it is a rare case of participation not only of the Academy of Sciences, but also of the Supreme authority, the Cabinet of Ministers, and the future teacher skillfully used the opening of the first school in the Urals, a remote region from the capital, to consolidate the most favorable working conditions. On the basis of a reconstruction of the full complex of archival documents deposited in the result of Stermer’s stay in Yekaterinburg, his activities on training children, the development of the program and teaching methods, writing instruction for teachers are revealed. His role in getting textbooks through the Academy of Sciences is characterized. The article comments on the implementation of the orders of the Ural authorities on the inspection in 1736 of schools, opened in the Perm region, as well as participation in the preparation of the Russian-Latin-German lexicon on the instructions of the head of the plants V. N. Tatishchev. It is shown that Stermer’s life in Yekaterinburg can be divided into two periods. Productive first years of work in the conditions of remoteness from the capital were replaced by depression, which resulted in drunkenness, rampant lifestyle and forced temporary release of the teacher from duty.